Changes and interruptions during COVID-19: caregivers of people with brain health challenges—A qualitative analysis - Kennedy, Polly; Rogan, Carol; Higgins, Dawn; Chen, Yao; Grycuk, Emilia; Leroi, Iracema; Wormald, Andrew; Galvin, Miriam (Frontiers in Dementia, 2024)
Background The social and economic challenges of the COVID-19 pandemic greatly impacted people's physical and mental health. The majority of care for individuals with brain health challenges, including dementia and mental illness, is provided by informal family caregivers. The “Coping with Loneliness, Isolation and COVID-19” (CLIC) Global Caregiver Survey 2020 received responses from over 5,000 caregivers across 50 countries of people living with enduring brain and/or physical health conditions. Aim This study examined English-speaking caregivers of people with brain health challenges (dementia and mental health conditions) descriptions of changes and interruptions in their ability to provide care in the context of the COVID-19 pandemic. Materials and methods Quantitative and qualitative data were collected as part of the large-scale CLIC Global Caregiver Survey. Data from over 900 English language respondents were analyzed using descriptive statistics and thematic content analysis. A multidisciplinary team of clinicians and health policy practitioners participated in team-based qualitative analyses. Results The majority of respondents were from the United States (71% USA), female (83%) and care providers to people living with dementia (81%). Respondents reported concerns about their loved one's physical and mental health, the limited access to other caregiving sources and the limited opportunities to maintain personal wellbeing. Practical, social, psychological and emotional impacts affected their ability to offer care. There was clear evidence that the disruption to health and social care services—institutions, day care and home services impacted the ability to offer care. Discussion The pandemic may be seen as a catastrophic “event” that negatively impacted lives and livelihoods. A number of the social determinants of health were negatively impacted for the caregivers surveyed during this prolonged period. Caring for caregivers and supportive health and social care interventions are required to maintain the wellbeing of this informal workforce. This study represents the largest, cross-country survey on the impact of the COVID-19 pandemic on caregivers of people with brain health challenges to date; serving as an important resource for support agencies and to inform policy.